What arguments on vaccinations run through YouTube videos in Italy? A content analysis - Loredana Covolo; Elisabetta Ceretti; Chiara Passeri; Michela Boletti; Umberto Gelatti (Taylor & Francis Group, 2017)
Background: The suspension of compulsory scheduling of some pediatric vaccines has been discussed for a long time by health authorities in Italy but the current decrease of vaccination rates is a matter of concern. YouTube is the most popular video-based social media website. Considering the demonstrated impact of internet on vaccination decision-making and the increasing use of social media to share and disseminate health information, the aim of this study was to explore the message available on YouTube videos about vaccination. Methods: An observational study was conducted searching for YouTube videos in September 2015 and updated in January 2016, by using the keyword "vaccinations." We included recently posted videos in Italian on child vaccination (2014-2015). Videos were classified according to the message tone. Results: A total of 123 videos were selected. Pro-vaccination videos were 62 (50%), anti-vaccination 28 (23%), neutral or without a clear position in favor or against vaccination 33 (27%). Focusing on the first 2 groups, pro-vaccination videos had a higher number of views compared with those unfavorable (1602 ± 6544 vs 1482 ± 2735) (p < 0.001). However, anti-vaccination videos were liked more by viewers (17.8 ± 31.3) than positive ones (13.2 ± 44.7) (p < 0.001) in addition to being more shared (23 ± 22.6 vs 3.8 ± 5.5, p < 0.001). Conclusions: Most of the videos were positive in tone, but those that disapproved of immunization were the most liked and shared. Considering the growing number of viewers, it is important to monitor the web to understand audience characteristics and what influences public opinions to use communication strategies more effectively.